Development of IOT-based Infant Incubator System with Temperature Detection - Kalidass, Shaunmhaathy; Wan Mahani Hafizah Wan Mahmud (Evolution in Electrical and Electronic Engineering, 2024)
This innovative project aims to improve existing infant incubators by creating a cutting-edge 3D model of an incubator housing using SolidWorks. Our main objective is to develop a completely automated solution that provides a reliable and controlled environment for premature newborns. Through the use of advanced technology such as DHT11 sensors, Arduino Durian Uno micro-controller, and IoT capabilities, our system ensures constant temperature regulation while minimizing the need for manual intervention. With a user-friendly software design and the inclusion of an IoT platform, this incubator offers effortless data retrieval through a Wi-Fi module and display on the Blynk mobile application, making it a truly state-of-the-art solution.The application not only accurately records and displays important temperature measurements, but also utilizes a responsive fan system, among other automated controls, to maintain an ideal incubator environment. By integrating state-of-the-art sensor technologies and IoT connectivity, this innovative infant incubator system strives to elevate neonatal care and create a safer and more efficient healthcare environment for infants.